LUXURY BRAND SOCIAL MEDIA MARKETING EFFORTS: INFLUENCE ON CONSUMER RESPONSE (CASE STUDY OF BUTTONSCARVES BIREUEN REGENCY) - Alifa Azeda; Hamdiah (RADJA PUBLIKA, 2024)
This study examines the influence between entertainment, interaction, trendy, customization, and word of mouth variables on consumer responses. The sample in this study was 110 people who had purchased bottonscraves products in Bireuen Regency. The analysis tool used is multiple linear regression. The results showed that each variable, entertainment, trendy and customization had a positive and significant effect on consumer response and there were two other variables namely interaction and word of mouth which had a significant negative effect on consumer response.